DOP44 Long term outcomes of patients with untreated IBD - A population-based analysis from the epi-IIRN. (27th May 2021) - Magen Rimon, R; Atia, O; Friss, C; Ledderman, N; Greenfeld, S; Kariv, R; Loewenberg Weisband, Y; Gabay, C; Shaoul, R; Odes, S; Matz, E; Dotan, I; et al.
Abstract: Background: Therapy in IBD is recommended in order to treat or prevent complications. In this nationwide study we aimed to assess the incidence of patients with IBD who were not receiving maintenance treatment after diagnosis and the duration of non-treatment. Methods: This study was performed on data from four Health Maintenance Organizations (HMOs), covering 98% of the Israeli population. We included all patients with IBD diagnosed from 2005 to 2019. Non-treatment was defined as lack of drug prescription of maintenance medication for at least six months from diagnosis. Sustainability was defined as lack of maintenance medications and without IBD-related surgeries. Cox regression model was used to explore estimated predictors of sustainability. Results: A total of 30, 168 patients were diagnosed with IBD in Israel since 2005 (16, 936 [56%] Crohn's disease [CD] and 13, 231 [44%] ulcerative colitis [UC]). A total of 5, 448 (32%) patients with CD were untreated, compared to 5, 158 (39%) with UC (OR 1.35 [95%CI 1.3–1.4]; p<0.001). Non-treatment was more likely in adult compared to pediatric-onset (34% vs 21%, respectively, p<0.001 in CD; and 41%% vs 22%, respectively, in UC; p<0.001) (Figure 1). Sustainability rate in CD was 72%, 46%, 36% and 28% after one, two, five and ten years from diagnosis, while in UC the corresponding rates were 59%, 39%, 24% and 16%. In CD, sustainability was associated with older age at diagnosis (HR 0.996 [95%CI 0.994–0.998]) and no induction therapy (HR 0.7 [95%CI 0.6–0.9] compared to steroids). In UC, sustainability was associated only with female sex (HR 0.9 [95%CI 0.88–0.98]). Conclusion: Most patients with IBD eventually require maintenance therapy. Lack of maintenance treatment is more common in UC. Nevertheless, a third of patients with CD and one quarter with UC who had no medical treatment at six months from diagnosis remained untreated for five years, especially in older patients with CD and those who did not require induction therapy, suggesting milder disease.